LOCAL INTEGRATED FOODHUB AT KENJERAN AREA, SURABAYA - Kartikasari, Prisky
Surabaya is a coastal city with a large tourism potential, one of which is in the culinary tourism sector. Unfortunately, there is no center for culinary tourism in the coastal area of Kenjeran which is a potential area. In the Kenjeran region there are also auction and fish processing centers as well as an urban farming program from the Surabaya City Government, including tomato, chili, etc. in the area of Kenjeran and Bulak. But unfortunately, a lot of potential is less explored and facilitated in the Kenjeran area. This has an impact on slow economic development. In fact, great potential such as the urban farming owned by the city government itself is less exposed and is rarely known by the public. Therefore, it is necessary to have integrated facilities such as commercial centers, food courts, and tourist areas to develop the potential of the surrounding community and become a new tourist attraction in the city of Surabaya. This project will be built on an area of 11,000m2 located on the road of the new Wedi pond, Kenjeran, Surabaya. The site area based on Surabaya's RDRTK is a commercial area with GSB 5m, KDB 50% and KLB 1.2. The design approach used is a function and context approach. Buildings are designed to accommodate diverse functions. This function approach is also carried out with user studies and aims to provide space and comfort experience for users. In addition, the approach in terms of context is also carried out with site studies that determine the orientation of the shape, material and layout of the building. The approach to building forms is also used in designing to produce attractive building shapes and spaces as recreational buildings. The shape of the building takes the form of a simple house with a gable as a response to the shape of surrounding buildings and also responds to the local climate so as to provide comfort for building users. This facility is designed to trigger active interactions implemented by the presence of commercial areas in the visitor's circulation area. This is also answered by the flow of circulation that is designed to pass through the plantation so that visitors who pass get a unique atmosphere of space and also see the process of community gardening directly. The mass of the building itself is divided into several zones based on groups of functions, namely Service, Dining Area, Retail, and Greenhouse. This foodhub was built to become an culinary educational recreation facility in Surabaya. This building is expected to be a place to meet various layers of society. Therefore, the building is made to have various functions that can accommodate functional business activities and present a unique atmosphere with views of the main sea and Suramadu Bridge for visitors. In addition, the existence of this facility also seeks the welfare of local farmers and the realization of educational tourism values.